Ter um filho oficial do exército: uma delegação transgeracional? - Molina, Silvana de Fátima Lima (2006)
Most studies about parents discuss the lack of interest by fathers, in emotional way, in their son s duties. However, these studies have shown trends towards the construction of a father s new role based on new gender perspectives. It raises a sensible father, and opened to dialogue. The military father and his family are not isolated from these social cultural modifications. As an Army Officer he will deal with hierarchy and discipline, as father, he will transmit delegations about personal and professional projects to their sons. The main focus of this research is to analyze the Army officer; fathers influence on his son s decision whether or not to follow the military career. This way 20 (twenty) cadets sons and grandsons of Army militaries form, that are studying at AMAN, were interviewed. The data were then transcribed and analyzed according to the technique to analyze content (MINAYO, 2004) where 12 (twelve) core of meaning was identified. These cores were categories that were spoted by the frequency that the cadets talked about, showed in accordance with the specific aims of the search, that were: to investigate, from military s sons view, the motivations and the feeling about the military career, as well, to identify easier and worst critical factors in this career and to analyze his expectations about his own son s future. So, we conclude through the cadet s interviews, how much powerful is the father s influence on the son s, decisions about personal and professional projects and choose to be an Army combatent officer. The frequency and the intensity of this image, of the father, military man is cultivated and legitimated as an object to be passed by through generation by generation was observed. Since a little boy, he understood the maybe identity as force and courage, represented, as well as, by rusticity of the male life and the uniform. Al though we know that we can t generalize the collected data, once it s a research of qualitative nature, we can any that this father systematically drives his son s routine, creating ouch a kind of mith these families around the to be a military establishing that the familiar goal ought to be to keep, at least, one of the sons as an Army s combatent officer in each generation. In order to have the delegation fulfilled and so to keep the commitment of to have Army officer sons it s necessary to be moved away, the son s move out from home to exclusive dedication to the militaries activities through the boarding school system in the Academy. It seems that should be, between family and son of agreement that once expulses the son and in the same time regency his way of life. Sons expect that this essay could contribute to the Military Psychology and other studies once there are few researches about this subjected, in Brazil